Clinical and Genetic Factors Associated With Complications After Crohn's Ileocolectomy. Issue 3 (March 2020) - Kline, Bryan P.; Weaver, Taelor; Brinton, David L.; Deiling, Sue; Yochum, Gregory S.; Berg, Arthur S.; Koltun, Walter A.
Abstract : BACKGROUND: Ileocolectomy is the most common surgery performed for Crohn's disease, and postoperative complications occur frequently. There has been minimal evaluation of complications after ileocolectomy as a function of both clinical and genetic factors. OBJECTIVE: The purpose of this study was to evaluate both genetic and clinical factors associated with complications after Crohn's ileocolectomy. DESIGN: This was a retrospective clinical and genetic cohort study. SETTINGS: This study was conducted at a high-volume tertiary care center. PATIENTS: We identified 269 patients with Crohn's disease who had undergone 287 ileocolectomies at our institution between July 2008 and October 2018. MAIN OUTCOME MEASURES: We measured the association of complications with a combination of clinical factors and 6 Crohn's-associated single nucleotide polymorphisms in NOD2 (rs2076756, rs2066844, and rs2066845), IRGM (rs4958847 and rs13361189), and ATG16L1 (rs2241880). RESULTS: There were 86 ileocolectomies of 287 (30%) with complications requiring intervention. The single nucleotide polymorphism rs13361189 in the gene IRGM was significantly associated with complications on univariate and multivariate analysis. There were 61 patients with a variant at the rs13361189 single nucleotide polymorphism and 26 of them had complications, although only 55 of the 208 wild-type patients had complications (43% vs 26%; OR = 2.1; p = 0.02). Other significant factors associated with complication after ileocolectomy were open surgery, placement of a proximal ileostomy, and a greater perioperative decrease in hematocrit. LIMITATIONS: This study was limited by its retrospective design and inherent selection bias. CONCLUSIONS: In addition to clinical risk factors, the rs13361189 single nucleotide polymorphism in the IRGM gene was independently associated with complications after ileocolectomy for Crohn's disease. The use of such genetic determinants may identify patients at increased risk for surgical complications after ileocolectomy. See Video Abstract at http://links.lww.com/DCR/B124 . FACTORES CLÍNICOS Y GENÉTICOS ASOCIADOS CON COMPLICACIONES DESPUÉS DE LA ILEOCOLECTOMÍA DE CROHN: ANTECEDENTES: La ileocolectomía es la cirugía más común realizada para la enfermedad de Crohn y con frecuencia ocurren complicaciones postoperatorias. Ha habido una evaluación mínima de complicaciones después de la ileocolectomía, en función de factores clínicos y genéticos. OBJETIVO: Evaluar factores genéticos y clínicos asociados con complicaciones, después de la ileocolectomía por Crohn. DISEÑO: Estudio retrospectivo de cohorte clínico y genético. AJUSTES: Este estudio se realizó en un centro de atención terciaria de alto volumen. PACIENTES: Identificamos a 269 pacientes con enfermedad de Crohn, sometidos a 287 ileocolectomías en nuestra institución, entre julio de 2008 y octubre de 2018. PRINCIPALES MEDIDAS DE RESULTADO: La asociación de complicaciones con una combinación de factores clínicos y seis polimorfismos de un solo nucleótido asociados a Crohn en NOD2 (rs2076756, rs2066844 y rs2066845), IRGM (rs4958847 y rs13361189) y ATG16L1 (rs2241880). RESULTADOS: Hubieron 86 ileocolectomías en 287 (30%) pacientes con complicaciones que requirieron intervención. El polimorfismo de un solo nucleótido rs13361189 en el gen IRGM se asoció significativamente con complicaciones en el análisis univariado y multivariado. Hubieron 61 pacientes con una variante en el polimorfismo de un solo nucleótido rs13361189 y 26 de ellos tuvieron complicaciones, mientras que solo 55 de los 208 pacientes de tipo salvaje (WT) tuvieron complicaciones (43% vs 26%, OR 2.1, p = 0.02). Otros factores significativos asociados con las complicaciones después de la ileocolectomía fueron, la cirugía abierta, la colocación de una ileostomía proximal y una mayor disminución perioperatoria del hematocrito. LIMITACIONES: Este estudio estuvo limitado por su diseño retrospectivo y sesgo de selección inherente. CONCLUSIONES: Además de los factores de riesgo clínicos, el polimorfismo de un solo nucleótido rs13361189 en el gen IRGM se asoció independientemente con complicaciones después de la ileocolectomía, para la enfermedad de Crohn. El uso de tales determinantes genéticos puede identificar a los pacientes con mayor riesgo de complicaciones quirúrgicas, después de la ileocolectomía. Consulte Video Resumen en http://links.lww.com/DCR/B124 .